1988
DOI: 10.1104/pp.87.2.510
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Production by Sunflower Cell Suspensions

Abstract: From a variety of undifferentiated plant cell suspensions, 2,4-dichlorophenoxyacetic acid-dependent cells of sunflower (Helianthus annuus L. Spanners Allzweck) produced large quantities of ethylene. The maximum rate was about 1 nanomole x gram fresh weight-' x hour-' during the exponential growth phase. The action of various compounds known to interfere with ethylene formation in plant tissue was studied in sunflower cell suspensions. The influence on ethylene, 1-aminocyclopropanecarboxylic acid (ACC), and N-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 10 publications
(24 reference statements)
0
17
0
2
Order By: Relevance
“…As previously shown, the growth-regulating potency of BAS l ll..W and other N-heterocyclic retardants is caused by an inhibition of cytochrome P-450-dependent monooxygenases particularly involved in gibberellin biosynthesis (Grossmann 1992;Rademacher 1992). In contrast, the interference of the compounds in ethylene biosynthesis was suggested to be caused either by a direct blockage of the ethylene-forming enzyme or by an indirect effect on cellular membrane properties (Sauerbrey et al 1988). …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…As previously shown, the growth-regulating potency of BAS l ll..W and other N-heterocyclic retardants is caused by an inhibition of cytochrome P-450-dependent monooxygenases particularly involved in gibberellin biosynthesis (Grossmann 1992;Rademacher 1992). In contrast, the interference of the compounds in ethylene biosynthesis was suggested to be caused either by a direct blockage of the ethylene-forming enzyme or by an indirect effect on cellular membrane properties (Sauerbrey et al 1988). …”
Section: Resultsmentioning
confidence: 97%
“…Data indicated that peak levels of ethylene during the exponential growth phase were synthesized by the cells via the ACC pathway (Sauerbrey et al 1988). No functional relation has been observed between growth of the culture and ethylene formation (Sauerbrey et al 1988).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sauerbrey et al (1988) afirmaram que os inibidores vegetais podem provocar a inibição da síntese do etileno, pois, em plântulas de girassol, a formação de etileno foi reduzida significativamente por triazóis. A inibição foi acompanhada pela elevação no nível de ACC (1-aminociclopropano-1-carboxílico), enquanto os níveis de N-malonil-ACC permaneceram inalterados, sugerindo que a conversão de ACC a etileno, catalisada pela enzima ACC oxidase, foi influenciada pelos inibidores vegetais.…”
Section: Resultsunclassified
“…Data suggested that at least the final steps in the ethylene synthesis of the cells are identical to those of intact plants (Sauerbrey et al 1988).…”
mentioning
confidence: 98%